2018
DOI: 10.1007/978-3-030-03189-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Characteristics as Described in Empirical Studies on Health Care

Abstract: The concept of resilience needs greater empirical clarity. The literature on resilience in health care, published between 2006 and 2016, was reviewed with the aim of describing resilient characteristics in empirical studies. The chapter documents resilient characteristics at the individual, team, management, and organizational level. The characteristics were related to four overall conceptual categories: anticipation, sensemaking, trade-offs and adaptation. Based on empirical accounts resilience is described a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 19 publications
3
68
0
3
Order By: Relevance
“…A recent review study [29], has explored what key concepts or characteristics are used in resilience in healthcare studies and identified that common resilience characteristics exist across system levels (macro, meso, micro). These relate to anticipation (i.e.…”
Section: A Brief Overview Of Key Constructs In Resilience Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review study [29], has explored what key concepts or characteristics are used in resilience in healthcare studies and identified that common resilience characteristics exist across system levels (macro, meso, micro). These relate to anticipation (i.e.…”
Section: A Brief Overview Of Key Constructs In Resilience Engineeringmentioning
confidence: 99%
“…This implies the potential for a common terminology for resilience characteristics across system levels, although they may describe somewhat different contents. To illustrate, Berg and Aase [29] discuss both individual cognitive tradeoffs and competing goals trade-offs at the team level.…”
Section: A Brief Overview Of Key Constructs In Resilience Engineeringmentioning
confidence: 99%
“…In addition, this study reflect that these structures must be present for all professional groups While self-organisation is an example of emergent behaviour utilized to adapt to complex work settings (15), self-organising in response to a lack of formal support systems leaves the system brittle. Relying too heavily on individuals' capacity to adapt will eventually cause overload and burnout (18).…”
Section: Managing Uncertaintymentioning
confidence: 99%
“…HCPs make such adaptations by relying on their skills, knowledge and experience (15), and they go beyond their assigned tasks and roles to adapt to challenges and changes in everyday practice (16,17). Studies of clinical decision-making in complex care settings have found that HCPs constantly make trade-offs between competing goals, adapt to complete their work, and apply sense-making skills to increase their situational awareness of ill-structured situations (18). These strategies also apply to successful suicide risk detection and response.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have proposed other resilience capabilities, such as rebound from unexpected events and return to equilibrium, robustness [17], planning, adapting, and noticing [18]. Berg and Aase (2019) conceptualised resilience in healthcare based on four categories: anticipation, sense making, trade-offs and adaptations, and defined it as a set of cognitive and behavioural strategies enacted by individuals within an organisational context [19]. Patriarca et al (2018) highlighted the importance of developing more advanced safety-oriented models to study resilience in order to overcome the limitations of the traditional safety approaches [15].…”
Section: Introductionmentioning
confidence: 99%